The Extraction of Nickel from Morowali Laterite Ore with Nitric Acid - I W. A. Wirawan; Daud K. Walanda; Mery Napitupulu (Jurnal Akademika Kimia, 2022)
Nickel extraction from Morowali laterite ore has been carried out with nitric acid as the solvent. This study aims to determine the effect of nitric acid concentration, temperature, and stirring time on nickel content in laterite ore originating from Morowali. Morowali laterite seeds were extracted using the leaching method using nitric acid as the solvent with various concentrations of 0.5, 1, and 2, temperatures of 30, 60, and 95, and stirring times of 3, 6, and 12. Taguchi analysis was used in this study to obtain the effect of the three parameters used. The results showed that the optimum conditions were obtained at a concentration of 2 molars nitric acid, a temperature of 95°C, and a stirring time of 12 hours, with a nickel content of 16.469 ppm and a nickel recovery percent of 3.88%.